Principals' level of computer use and some contributing factors - Afshari, Mojgan; Abu Bakar, Kamariah; Wong, Su Luan; Afshari, Marjan (North Atlantic Univeristy Union, 2010)
This study identified the extent to which Iranian secondary school principals use computers and explored the relationship between three variables related to ICT use. These factors included high level of computer access, positive attitudes towards ICT, and positive cultural perceptions of ICT, all contributed significantly to the computer use by principals. Findings from this study indicated that principals spent a few times a week working on their computers. It seems that knowledge of the role of ICT in the work life of the school principals and the acquisition of appropriate skills to use this knowledge needs to be understood by the principals. Hence, considerable ongoing professional development opportunities should be provided for principals to fulfill their role as technology leaders.